2001
DOI: 10.1034/j.1600-0463.2001.d01-117.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate and biofilm thickness of Streptococcus sobrinus and Streptococcus mutans on hydroxapatiteNote

Abstract: Bacteria in biofilm and planktonic bacteria exhibit different properties. The objective of the present study was to compare the growth rates of Streptococcus sobrinus and Streptococcus mutans on different types of biofilm with their planktonic growth rate. Our experimental model consisted of hydroxyapatite beads coated with human saliva (sHA). Glucans or fructans were synthesized in situ on sHA by immobilized cell-free glucosyltransferase or fructosyltransferase isolated from oral bacteria. S. sobrinus or S. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 16 publications
(24 reference statements)
3
18
0
Order By: Relevance
“…The efficiency of GAS biofilm formation after 24 h, measured in log CFU, was normally distributed with a range of 10 (22,30,32). However, no other studies have looked at a variety of isolates of the same species.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The efficiency of GAS biofilm formation after 24 h, measured in log CFU, was normally distributed with a range of 10 (22,30,32). However, no other studies have looked at a variety of isolates of the same species.…”
Section: Discussionmentioning
confidence: 97%
“…This finding indicated that there was a spectrum of capacities for GAS isolates to initiate or expand the biofilm. Factors that contribute to the initiation and expansion of biofilms are numerous; some examples include the capability to adhere to the substratum (12), quorum sensing (19), growth rate (32), and establishing a biofilm structure (30,35). Using the total number of cells in the biofilm to measure efficiency was insufficient to establish the factor(s) that would assist in explaining the variation observed in the efficiency of GAS biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, 40 mg of HA beads (80 m in diameter) (BioRad Laboratories, Hercules, CA) were equilibrated with phosphate-buffered-saline (PBS) and incubated for 1 h at 37 • C with clarified whole saliva. After three washes with PBS, the saliva-coated HA (sHA) were incubated for 1 h at 37 • C with cell-free GTF or FTF, prepared as described by Rozen et al [14]. The saliva and enzyme-coated HA beads were washed three times with PBS and further incubated at 37 • C with radioactively labelled S. sobrinus ( 3 H radiolabelled bacteria were prepared by supplementing the bacterial growth medium with 5 mci/ml of 3 H-thymidine.…”
Section: Effect Of Ndm On Bacterial Detachment From Biofilmsmentioning
confidence: 99%
“…Previous results demonstrated that S. mutans is able to form a biofilm on hydroxyapatite in vitro (28). Hydroxyapatite is composed of a complex calcium phosphate mineral and is a principal component found in tooth enamel.…”
Section: Resultsmentioning
confidence: 96%